1985
DOI: 10.1002/hep.1840050320
|View full text |Cite
|
Sign up to set email alerts
|

Oral, nonabsorbable antibiotics prevent infection in cirrhotics with gastrointestinal hemorrhage

Abstract: To investigate if oral, nonabsorbable antibiotics prevent bacterial infections in cirrhotics with gastrointestinal hemorrhage, 140 consecutive patients were randomly allocated into two groups: 68 patients (Group I) were given oral, non absorbable antibiotics (gentamicin + vancomycin + nystatin or neomycin + colistin + nystatin) from the inclusion into the trial up to 48 hr after cessation of the hemorrhage, or until emergency surgery or death in those cases who continued bleeding; and 72 patients (Group II) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
3
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(138 citation statements)
references
References 21 publications
7
122
3
6
Order By: Relevance
“…O uso profilático da norfloxacina de forma mais rotineira nos pacientes com episódio prévio de PBE (42) , nos com proteínas baixa no líquido de ascite (16) e nos com hemorragia digestiva alta, também deveria ter contribuído para a diminuição mais significativa da incidência desta infecção (16,17,33) . Ressalve-se que na reunião do Clube Internacional de Ascite, onde foram definidos os critérios para o diagnóstico, tratamento e profilaxia da PBE, não houve consenso quanto à realização de profilaxia primária a pacientes com proteínas baixas no líquido de ascite (35) .…”
Section: Discussionunclassified
“…O uso profilático da norfloxacina de forma mais rotineira nos pacientes com episódio prévio de PBE (42) , nos com proteínas baixa no líquido de ascite (16) e nos com hemorragia digestiva alta, também deveria ter contribuído para a diminuição mais significativa da incidência desta infecção (16,17,33) . Ressalve-se que na reunião do Clube Internacional de Ascite, onde foram definidos os critérios para o diagnóstico, tratamento e profilaxia da PBE, não houve consenso quanto à realização de profilaxia primária a pacientes com proteínas baixas no líquido de ascite (35) .…”
Section: Discussionunclassified
“…[19][20][21][22][23][24][25][26][27][28] Initial studies showed that infections in cirrhotic patients receiving prophylactic norfloxacin were almost exclusively caused by gram-positive cocci, mainly streptococci, and gram-negative bacilli were rarely isolated, [20][21][22] as a result of the antimicrobial spectrum of norfloxacin. 49 However, it has recently been suggested that prophylaxis with norfloxacin would favor the development of infections caused by gram-negative bacilli resistant to norfloxacin in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Several controlled clinical trials have shown the efficacy of antibiotic prophylaxis, mainly selective intestinal decontamination with oral norfloxacin, in the prevention of SBP and other bacterial infections in cirrhotic patients at high risk of infection. [19][20][21][22][23][24][25][26][27][28] These studies showed changes in the bacteria responsible for the infections, because cirrhotic patients submitted to prophylaxis with norfloxacin were infected almost exclusively by gram-positive cocci and gram-negative bacilli were rarely observed because of the apparent absence of resistance to quinolones by these bacteria. [19][20][21][22][23][24]29 However, recent studies have shown an increasing incidence in the resistance of gram-negative bacilli to quinolones in the general population, [30][31][32] as well as in neutropenic [33][34] and cirrhotic 23,35,36 patients submitted to prophylaxis with these antibiotics.…”
mentioning
confidence: 98%
“…[24] Antibiotic prophylaxis has been shown to prevent infection in patients with gastrointestinal bleeding and decrease the rate of rebleeding. A meta-analysis of five studies performed in patients with gastrointestinal bleeding [25][26][27][28][29] has shown that antibiotic prophylaxis significantly decreased both the incidence of severe infections (SBP and/or sepsis) and mortality. The preferred antibiotic for SBP prophylaxis is norfloxacin (400 mg/12 h orally for 7 days) which provides selective intestinal decontamination.…”
Section: Sepsis In Liver Cirrhosismentioning
confidence: 99%